2014
DOI: 10.1136/annrheumdis-2013-204767
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic and cardiovascular risk in rheumatoid arthritis: role of the haemostatic system

Abstract: Circumstantial evidence suggests that the innate immune system and coagulation system share a common evolutionary origin, which explains the extensive crosstalk between inflammatory cytokines and coagulation factors, with many components being important for both systems. This crosstalk has been extensively studied in sepsis, an acute state of high-grade inflammation. However, rheumatoid arthritis (RA) as well as many other autoimmune diseases can also be considered as a prothrombotic state. More and more studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 27 publications
1
50
0
4
Order By: Relevance
“…It has been reported that autoimmune diseases such as RA, ankylosing spondylitis, and lupus nephritis are associated with disorders of coagulation system [15][16][17]. There are studies showing that coagulation is activated in the joint of RA patients [15,18], and alterations in levels of coagulation factors have been related to vascular disease in RA [19]. Fibrinogen (FIB) is a key factor implicated in the process of blood coagulation cascade, and its deposition in the joint was recognized to be characteristic of RA and even may be responsible for the formation of pannus tissue [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that autoimmune diseases such as RA, ankylosing spondylitis, and lupus nephritis are associated with disorders of coagulation system [15][16][17]. There are studies showing that coagulation is activated in the joint of RA patients [15,18], and alterations in levels of coagulation factors have been related to vascular disease in RA [19]. Fibrinogen (FIB) is a key factor implicated in the process of blood coagulation cascade, and its deposition in the joint was recognized to be characteristic of RA and even may be responsible for the formation of pannus tissue [15].…”
Section: Introductionmentioning
confidence: 99%
“…ТЦЗ и система коагуляции. Активация каскада коагуляции является одним из этапов ССО у больных РА [101]. ИЛ-6 и α-ФНО -основные провоспалительные цитокины, которые ассоциируются с тромбоэмболическими осложнениями.…”
Section: терапевтический архив 5 2016unclassified
“…This is associated with activation of ERK signaling pathway and overexpression of survivin. This possibly leads to alterations of RBC homeostasis that, together with increased ESR and inflammatory protein CRP 10 , could alter blood flow 1 …”
Section: To the Editormentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is an autoimmune inflammatory disease that can be considered as a prothrombotic state 1 . A great number of studies have investigated the possible role of reactive oxygen species (ROS) in the etiology and pathogenesis of this disease.…”
Section: To the Editormentioning
confidence: 99%